Low Serum-Derived Syncytin-2 Levels in Exosome at Early Pregnancy is a Predictor of Preeclampsia: A Prospective Pilot Study in Benin, West Africa - LOKOSSOU, GATIEN; Davito, Lucien; BADAROU, Amyrath; ACCROMBESSI, Manfred; AZONNAKPO, Julien; KOUNOUDJI, Giscarde; LOSEZ, Evelyne Josette Marie; ossou-Gbété, Lucien; HOUNKPATIN, BENJAMIN IGNACE B.; PERRIN, RENÉ-XAVIER; Barbeau, Benoit (My University, 2020)
Preeclampsia (PE) affects 2 to 8% of pregnant women and represents one of the major causes of maternal and perinatal morbidity and mortality, particularly in sub-Saharan Africa. A limited number of biomarkers have been proposed for the identification of pregnant women predisposed to preeclampsia. Syncytin-2 is an endogenous retrovirus envelope protein playing a key role in placental formation through the fusion of villous cytotrophoblasts, resulting in syncytiotrophoblast formation. The reduction of Syncytin-2 levels detected in placental tissue and on the surface of exosomes has been shown to strongly correlate with the severity of symptoms in preeclamptic patients. We were thus interested in conducting an analysis of a Benin cohort of pregnant women over the predictive value of this marker. From July 2015 to January 2017, 260 pregnant women were recruited in two health facilities. Blood samples were monthly collected from the beginning of pregnancy up to 20 weeks of gestation and exosomes were then isolated. We then compared Syncytin-2 levels in exosome preparations from women who presented PE to those with normal pregnancy. Our results showed that Syncytin-2 significantly decreased between 7 to 10 weeks of gestation in pregnant women with PE compared to normal pregnant women (p=0.02). Our study thereby suggests that Syncytin-2 could be a promising biomarker for early diagnosis of PE.
Keywords: Pregnancy; Preeclampsia; Early diagnosis; Exosomes; Syncytin-2.